Predicting Mucosal Proliferation in Ulcerative Colitis by Assessing Mucosal Vascular Pattern Under Narrow Band Imaging Colonoscopy - Guo, Tao; Qian, Jia-Ming; Yang, Ai-Ming; Li, Yue; Zhou, Wei-Xun (Turkish Journal of Gastroenterology, 2021)
Background: Proliferative abnormalities are believed to represent an early phase of colorectal carcinogenesis. Narrow band imaging (NBI) colonoscopy allows visual assessment of the mucosal vascular pattern (MVP) without dyeing. The aim of this study was to investigate the predictive value of MVP for mucosal proliferation in ulcerative colitis (UC).Methods: A total of 119 colorectal lesions were analyzed from 42 patients with UC who underwent NBI colonoscopy. Both the MVP and the Mayo endoscopic score (MES) were assessed. The mucosal inflammation was histologically graded using a colitis score. The proliferation marker Ki-67 was assessed by immunohistochemical staining.Results: The results showed that MVP correlated well with the MES (r = 0.796, P < .001). There was moderate correlation between the distribution of Ki-67 staining and MVP (r = 0.492, P < .001), and the Ki-67 labeling index increased with the orderly patterns of MVP (P < .001). An expansion of Ki-67 staining upward from the crypt base may be caused by active inflammation.Conclusion: MVP based on NBI colonoscopy can predict mucosal proliferation which is associated with inflammation in patients with UC.